Safety and efficacy of minimal biliary sphincterotomy with papillary balloon dilation (m-EBS+EPBD) in patients using clopidogrel or anticoagulation - Mok, Shaffer R. S.; Arif, Murtaza; Diehl, David L; Khara, Harshit S; Ho, Henry C; Elfant, Adam B (Endoscopy International Open, 2017)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) with endoscopic biliary sphincterotomy (EBS) or endoscopic papillary balloon dilation (EPBD) are common techniques of biliary decompression. Potential risks include gastrointestinal hemorrhage, which can be increased by antiplatelet agents, anticoagulants (AC) and/or novel oral anticoagulants (NOACs) (ie. apixaban, dabigatran and rivaroxaban). The study aim is to evaluate the safety/efficacy of an alternative technique, minimal-EBS plus EPBD (m-EBS + EPBD), in individuals for whom clopidogrel, AC, and/or NOACs cannot be interrupted due to high cardiovascular or thromboembolic risk.Patients and methods Patients undergoing m-EBS + EPBD while taking clopidogrel and/or AC were retrospectively evaluated at two United States tertiary care centers for efficacy, GIB and procedure-related, cardiovascular and thromboembolic adverse events (AE).Results Ninety-five patients were identified [55 = clopidogrel and 45 = AC (31.1 % NOACs)]. The main indication for ERCP was choledocholithiasis (34 %). 100 % clinical improvement and 97.9 % endoscopic success were found. The incidence of AE was 5.3 %. There was a 4.2 % incidence of gastrointestinal hemorrhage (2 cases requiring endoscopic intervention). Both severe gastrointestinal hemorrhages also experienced the cases of post-ERCP pancreatitis, and 2 /3 of cholangitis (all aspirin + AC). There was 1cardiovascular event (non-ST elevation myocardial infarction), and no thromboembolic events. Conclusions Minimal-EBS + EPBD is an effective and safe therapy with an incidence of gastrointestinal hemorrhage of 4.2 %, (2.1 % requiring endoscopic intervention), for patients on clopidogrel and/or AC, with a high risk for cardiovascular/thromboembolic events.